2014
DOI: 10.1007/s00586-014-3223-0
|View full text |Cite
|
Sign up to set email alerts
|

Does sagittal position of the CTDR-related centre of rotation influence functional outcome? Prospective 2-year follow-up analysis

Abstract: Our results confirm the influence of CORi location on segmental alignment, kinematics and HO for a semi-constrained CTDR, but it also indicates a multifactorial process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…51 The clinical relevance of HO is controversial, indicating that HO does not affect clinical improvement 5,33,38,51,52,57 and is less relevant in the absence of clinical symptoms, 6,28 while challenging the principle of motion preservation. On the other hand, most studies show that in the majority of patients segmental mobility was sustained 4 to 6 years after cTDR.…”
Section: Discussionmentioning
confidence: 99%
“…51 The clinical relevance of HO is controversial, indicating that HO does not affect clinical improvement 5,33,38,51,52,57 and is less relevant in the absence of clinical symptoms, 6,28 while challenging the principle of motion preservation. On the other hand, most studies show that in the majority of patients segmental mobility was sustained 4 to 6 years after cTDR.…”
Section: Discussionmentioning
confidence: 99%
“…However, in longer term follow-up, ROM became comparable to preoperative values [30,58,[64][65][66][67]. Other studies have reported preserved segmental ROM compared with preoperative ROM at 1-2year [14,20,55,[69][70][71][72], 3-5-year [73][74][75][76][77][78][79][80], 7-year [81], and 8-year follow-up [82]. Interestingly, some studies even reported significantly more mobile segments over 1-year follow-up [48] than at 5-year follow-up [83].…”
Section: Does Heterotopic Ossification Really Matter To Patients In Cmentioning
confidence: 80%
“…Significant changes in postoperative COR-X and COR-Y have been reported in another study examining ProDisc-C and Synergy prostheses [35]. Indeed, a more posterior COR was correlated with a higher rate of HO [20]. Tu et al [2] suggested that surgeons should place implants at the center of the disc space, with symmetrical disc space from the sides.…”
Section: Center Of Rotationmentioning
confidence: 94%
See 1 more Smart Citation
“…However, even patients with a physiological cervical alignment and adequate decompression can display certain amounts of persisting neck pain and neurological dysfunction, as evidenced even in patients undergoing total disc arthroplasty that display only slight degenerative changes [32]. Kyphotic patients can be asymptomatic, as well [26].…”
Section: Discussionmentioning
confidence: 99%